Evaluation of 2‐Hour Post‐Dose Efficacy of Lasmiditan for the Acute Treatment of Difficult‐to‐Treat Migraine Attacks. Issue 8 (7th July 2020) - Tepper, Stewart J.; Vasudeva, Raghavendra; Krege, John H.; Rathmann, Suchitrita S.; Doty, Erin; Vargas, Bert B.; Magis, Delphine; Komori, Mika
Abstract : Objective: To identify factors predicting response (2‐hour headache pain freedom or most bothersome symptom freedom) to lasmiditan based on individual patient characteristics, migraine disease characteristics, and migraine attack characteristics. Further, efficacy specifically in difficult‐to‐treat patient/migraine disease characteristics or attack characteristics (ie, historically considered less responsive to certain acute therapies) subgroups was analyzed. Background: Knowledge of factors associated with a positive or negative response to acute treatment would be useful to practitioners prescribing acute treatments for migraine. Additionally, practitioners and patients would benefit from understanding the efficacy of lasmiditan specifically in subgroups of patients with migraine disease characteristics and migraine attack characteristics historically associated with decreased pain threshold, reduced efficacy of acute treatment, or increased burden of migraine. Methods: Pooled analyses were completed from 2 Phase 3 double‐blind clinical trials, SPARTAN and SAMURAI. Data from baseline to 2 hours after taking lasmiditan (50, 100, or 200 mg) or placebo were analyzed to assess efficacy based on patient characteristics, migraine disease characteristics, and migraine attack characteristics. A total of 3981 patients comprising the intent‐to‐treat population were treated with placebo (N = 1130), lasmiditan 50 mg (N = 598), lasmiditan 100 mg (N = 1133), or lasmiditan 200 mg (N = 1120). Data were analyzed for the following efficacy measures at 2 hours: headache pain freedom and most bothersome symptom freedom. Results: None of the analyzed subgroups based on individual patient characteristics, migraine disease characteristics, or migraine attack characteristics predicted headache pain freedom or most bothersome symptom freedom response at 2 hours following lasmiditan treatment (interaction P ≥ .1). For the difficult‐to‐treat patient/migraine disease characteristics subgroups (defined as those with ≥24 headache days in the past 3 months, duration of migraine history ≥20 years, severe disability [Migraine Disability Assessment score ≥21], obesity [≥30 kg/m 2 ], and history of psychiatric disorder), single doses of lasmiditan (100 or 200 mg) were significantly more effective than placebo ( P ≤ .002) in achieving both endpoints. Headache pain freedom response rates for higher doses of lasmiditan were numerically greater than for lower doses of lasmiditan. For the difficult‐to‐treat migraine attack subgroups, patients with severe headache, co‐existent nausea at the time of treatment, or who delayed treatment for ≥2 hours from the time of headache onset, both endpoint response rates after lasmiditan 100 or 200 mg were significantly greater than after placebo. Among those who delayed treatment for ≥4 hours from the time of headache onset, headache pain freedom response rates for the 200 mg dose of lasmiditan met statistical significance vs placebo (32.4% vs 15.9%; odds ratio = 2.7 [1.17, 6.07]; P = .018). While the predictors of response interaction test showed similar efficacy of lasmiditan vs placebo across subgroups defined by baseline functional disability (mild, moderate, or needs complete bed rest) at the time of treatment, analyses of lasmiditan efficacy within the subgroup "needs complete bed rest" appeared to show less efficacy (eg, in the 200 mg vs placebo group, 25.9% vs 18.5%; odds ratio = 1.56 [0.96, 2.53]; P = .070). Conclusions: Efficacy of lasmiditan 200 and 100 mg for headache pain freedom and most bothersome symptom freedom at 2 hours post‐treatment was generally not influenced by the individual patient characteristics, migraine disease history, or migraine attack characteristics that were analyzed. In the analyses of difficult‐to‐treat subgroups, patients receiving lasmiditan achieved greater responses (2‐hour headache pain freedom and most bothersome symptom freedom) vs placebo recipients.